Recent insights into the function of autophagy in cancer - Amaravadi, Ravi; Kimmelman, Alec C.; White, Eileen (Genes & development, 2016)
Macroautophagy (referred to here as autophagy) is induced by starvation to capture and degrade intracellular proteins and organelles in lysosomes, which recycles intracellular components to sustain metabolism and survival. Autophagy also plays a major homeostatic role in controlling protein and organelle quality and quantity. Dysfunctional autophagy contributes to many diseases. In cancer, autophagy can be neutral, tumor-suppressive, or tumor-promoting in different contexts. Large-scale genomic analysis of human cancers indicates that the loss or mutation of core autophagy genes is uncommon, whereas oncogenic events that activate autophagy and lysosomal biogenesis have been identified. Autophagic flux, however, is difficult to measure in human tumor samples, making functional assessment of autophagy problematic in a clinical setting. Autophagy impacts cellular metabolism, the proteome, and organelle numbers and quality, which alter cell functions in diverse ways. Moreover, autophagy influences the interaction between the tumor and the host by promoting stress adaptation and suppressing activation of innate and adaptive immune responses. Additionally, autophagy can promote a cross-talk between the tumor and the stroma, which can support tumor growth, particularly in a nutrient-limited microenvironment. Thus, the role of autophagy in cancer is determined by nutrient availability, microenvironment stress, and the presence of an immune system. Here we discuss recent developments in the role of autophagy in cancer, in particular how autophagy can promote cancer through suppressing p53 and preventing energy crisis, cell death, senescence, and an anti-tumor immune response.